Partisipasi Perempuan dalam Pangan Agroforestri di Kalimantan Tengah: Tantangan dan Hambatan - Nur Dwiyati (Yayasan Jurnal Perempuan, 2022)
Food Agroforestry is one element of the National Economic Recovery Program, which aims to counter the effects of the Covid-19pandemic by protecting the economy and promoting food security. The agroforestry program targets Social Forestry Business groupswith forest utilization activities. Support is provided in the form of productive economic tools and food agroforestry assistance. Thispaper examines the involvement of women in food agroforestry activities. The research applies the descriptive approach for secondarydata related to food agroforestry activities and interviews with female leaders who are involved in forest management activitiesand group business development. The results of the analysis show that food agroforestry activities provide economic, ecological,and social benefits for the community. Further, these activities provide access for women to be involved in forest management andutilization, and to support food security and family economies.